The bactericidal hydrogel materials and soft contact lenses on their bases - Skorokhoda, V. Y.; Semenyuk, N. B.; Melnyk, Yu. Ya.; Dzjaman, I. Z.; Suberlyak, O. V. (Видавництво Львівської політехніки, 2016)
A hydrogel polymeric material with bactericidal properties based on 2-hydroxyethyl methacrylate and polyvinylpyrrolidone copolymers for soft contact lenses was developed. The regularities of copolymers obtaining by the graft copolymerization reaction, which occurs through a stage of complex formation between the reagents, were investigated. The relation between the complexation constant, the polymerization reaction kinetic parameters and structural parameters of the copolymers grid were established. The basic performance properties of hydrogels depending on their composition were investigated. The effect of silver nanoparticles on hydrogel coefficient of light permeability and its antibacterial properties were determined. Розроблено гідрогелевий полімерний матеріал із бактерицидними властивостями на основі кополімерів 2-гідроксіетилметакрилату з полівінілпіролідоном для м’яких контактних лінз. Досліджено закономірності одержання кополімерів реакцією прищепленої кополімеризації, яка відбувається через стадію комплексоутворення між реагентами. Встановлено взаємозв’язок між константою комплексоутворення, кінетичними параметрами реакції полімеризації і структурними параметрами сітки кополімерів. Досліджено основні експлуатаційні властивості гідрогелів залежно від їх складу. Досліджено вплив наночастинок срібла на світлопропускання гідрогелю та його бактерицидні властивості.
Бактерицидні гідрогелеві матеріали і м’які контактні лінзи на їхній основі
Keywords: contact lenses; polyvinylpyrrolidone; 2-hydroxyethy methacrylate; hydrogel; permeability; контактні лінзи; полівінілпіролідон; 2-гідроксіетилметакрилат; гідрогель; проникність